The influence of the lever fixturing of the vibration exciter on the overall efficiency of concrete-mix vibration - Korobko, Bogdan; Korotych, Yuriy (Academic journal Industrial Machine Building Civil Engineering, 2021)
The article presents the design of the compaction table with the option of fixing the vibration exciter on the lever, providing that there is free space under it (when fixing the compaction table on the supporting structure above the floor line). The authors have conducted research on a specially created research model, aimed at determining the dependence of the amplitude of vibration on the lever length, on which the vibration exciter is fixed, and on the load on the moving member of the compaction table. A research model of the compaction table with lever fixturing of the vibration exciter was created in order to conduct research and obtain measurement results. The results of the conducted research have shown that with increasing the length of the lever, on which the vibration exciter is fixed, the values of the shock pulses acting on the vibratory plate increase accordingly, and the increase in the load leads to the decrease in the magnitude of the shock pulses. The obtained results provide an opportunity to reduce energy consumption in production and to continue further research in this study area.